Genomic and functional insights into Lactiplantibacillus plantarum UTNGt3 from Ecuadorian Amazon Chrysophyllum oliviforme: a safe and promising probiotic - Tenea, Gabriela N.; Hidalgo, Jazmin; Pircalabioru, Gratiela Gradisteanu; Cifuentes, Victor (Frontiers in Microbiology, 2025)
IntroductionLactiplantibacillus plantarum is a versatile lactic acid bacterium (LAB) recognized for its probiotic potential, with key traits such as adhesion to intestinal epithelial cells and tolerance to bile salts and gastric acid being essential for its efficacy. In this study, we isolated and characterized L. plantarum strain UTNGt3 from Chrysophyllum oliviforme (Caimitillo) fruits collected in the Ecuadorian Amazon.MethodsWhole-genome sequencing, gene annotation, and in silico analyses were performed to explore genomic architecture, identify probiotic gene markers (PGMs), and assess safety features, including bacteriocin gene clusters (BGCs). In vitro assays evaluating bile salt and acid tolerance, cell surface hydrophobicity, auto-aggregation, and adhesion to Caco-2 intestinal epithelial cells were conducted to characterize probiotic traits. Additionally, the biocompatibility of UTNGt3 external metabolites was assessed using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay and LDH (lactate dehydrogenase) release assay on intestinal cells.ResultsUTNGt3 genome spans 3,569,352 bp with 43.95% GC content. EggNOG analysis showed enrichment in genes related to general function prediction (11.89%), carbohydrate metabolism (8.97%), and transcription (8.45%), with 25.92% annotated as hypothetical proteins. No acquired antibiotic resistance or virulence genes were detected. Genome mining revealed three BGCs, plantaricin_N, enterolysin_A, and plantaricin_W-beta, associated with antimicrobial functions. Diverse PGMs involved in stress tolerance, adhesion, and vitamin biosynthesis were also identified. Phenotypic assays confirmed strong acid and bile tolerance, high auto-aggregation, surface hydrophobicity, and superior adhesion to Caco-2 cells compared to E. coli. Biocompatibility assays confirmed over 85% cell viability and minimal membrane damage, supporting their safety.ConclusionThese findings establish UTNGt3 as a safe, multifunctional probiotic candidate with potential for functional food applications and future gut health studies.